Development of Solar Powered LED Street Lighting with Auto Intensity Control - KUAMTHAB, NOR ELISYA; MUSTAFA, FARAHIYAH (Progress in Engineering Application and Technology, 2021)
Solar is a non-conventional source of energy, and by using a charge controller, electricity can be captured by solar panels and stored in batteries. There are times where the streetlight is not turned on and off in a suitable time. The streetlights are ON even during daytime and sometimes the streetlights will not be turned ON at night. This kind of situation directly will be increasing the street lighting cost. The purpose of the solar streetlight study is to develop a system that does not consume enormous amount of electricity, maintaining optimum use with minimum energy loss. The function of charge controller is to control the battery charging process. This stored energy is used throughout the night to illuminate the streetlight. Solar streetlights are designed to read the inputs from sensors and analyze them for desired output, based on Arduino Uno microcontroller as the controller. Two sensors used in this study are light dependent resistor (LDR) sensor and infra-red (IR) sensor. At dusk, streetlights can turn ON and automatically switch OFF at dawn, do not emit light when there is no motion, and emit light when it senses a movement of either the vehicle or people walking by. As the system in this study comes with a different situation, which is the streetlight will turn ON only if there is a vehicle or human passing through it, the electrical wastage and cost while operating the streetlight can be reduced. Based on the result, the streetlight at 5 ft of height produced 0.39 lx and 2.63 lx measured at actual and prototype, respectively with voltage 1:1. In this study, it shows that almost 85 % differences of lux at voltage ratio of 1:1 has been obtained